Investigating the Effectiveness of Educandy as Gamification in English Language Teaching to Improve Students' Vocabulary Mastery - Nur Ahista Balqist (Universitas Samudra, 2024)
The purpose of this study was to investigate whether the Educandy application effect the students’ vocabulary mastery. The study focused on the seventh-grade students of SMP N 2 Langsa, with sample of 44 students, divided into an experimental class and a control class. A quantitave approach was employed, utilizing a quasi-experimental design. The research instrument consisted of a vocabulary test, and the data were gathered through pre-test and post-test. Analysis was conducted using non-parametric tests, specifically the Wilcoxon and Mann-Whitney tests. The findings indicated a significant improvement in the mean scores of the experimental class after using the Educandy application compared to the control class. Statistical analysis yielded an Asymp Sig. (2-tailed) value of 0.000. which is less than α = 0.05, leading to the rejection of H0 and acceptance of Ha. Therefore, the study concluded that Educandy application effectively enhances students’ vocabulary mastery.